Profil Pembelajaran Digital Sekolah Dasar - Hotman Sugeng Ritonga; Banun Havifah Cahyo Khosiyono (Tuladha : Jurnal Pendidikan Dasar, 2022)
In the digital era or the current information age, science and technology are developing rapidly. This development has the impact of being more open and spreading information and knowledge from and to all over the world, breaking the boundaries of distance, place, space, and time. This is pursued through creative learning development and innovation activities in digital elementary learning activities that are expected to be able to foster student interest and motivation in learning. So that learning can be more interesting, fun, and meaningful. The purpose of writing the article is to describe elementary digital learning. This study uses a qualitative descriptive method with the results of the research in the form of descriptive analysis. The subjects studied were fifth grade students at Mutiara Hati Integrated Islamic Elementary School, totaling 10 students. Data collection techniques were carried out through interviews and observation techniques as well as documentation. Data analysis techniques were carried out using triangulation and drawing conclusions. The results of this study indicate that digital learning in elementary schools can provide opportunities for students to actively and creatively express ideas in participating in learning and not feel bored during learning.